Delivery of Eye and Vision Services in Aboriginal and Torres Strait Islander Primary Healthcare Centers - Burnett, Anthea M.; Morse, Anna; Naduvilath, Thomas; Boudville, Andrea; Taylor, Hugh R.; Bailie, Ross (Frontiers in Public Health, 2016)
Background: Routine eye and vision assessments are vital for the detection and subsequent management of vision loss, which is particularly important for Aboriginal and Torres Strait Islander people, who face higher rates of vision loss than other Australians. In order to guide improvements, this paper will describe patterns, variations and gaps in these eye and vision assessments for Aboriginal and Torres Strait Islander people. Methods: Clinical audits from 124 primary health care centres (sample size 15,175) from five Australian States and Territories were conducted during 2005-2012. Main outcome measure was adherence to current guidelines for delivery of eye and vision assessments to adults with diabetes, those without a diagnosed major chronic disease and children attending primary health care centres. Results: Overall delivery of recommended eye and vision assessments varied widely between health centres. Of the adults with diabetes, 45% had a visual acuity assessment recorded within the previous 12 months (health centre range 0-88%), and 33% had a retinal examination recorded (health centre range 0-73%). Of the adults with no diagnosed major chronic disease, 31% had a visual acuity assessment recorded within the previous two years (health centre range 0-30%), and 13% had received an examination for trichiasis (health centre range 0-40%). In children, 49% had a record of a vision assessment (health centre range 0-97%), and 25% had a record of an examination for trachoma within the previous 12 months (health centre range 0-63%). Conclusions: There was considerable range, and variation in the recorded delivery of scheduled eye and vision assessments across health centres. Sharing the successful strategies of the better-performing health centres to support focused improvements in key areas of need may increase overall rates of eye examinations – important for the timely detection, referral and treatment of eye conditions affecting Aboriginal and Torres Strait Islander people, especially for those with diabetes.